ChemInform Abstract: (N, N‐Diisopropylcarbamoyloxy)‐methyl p‐Tolyl Sulfone: Preparation and Application for the Syntheses of 1, 2‐Diols. Issue 9 (5th March 2013) - Ma, Lu; Zhao, Dongmei; Chen, Lin; Wang, Xin; Chen, Yue‐Lei; Shen, Jingkang
Abstract A convenient two‐step approach to the title sulfone (V) is presented.